Correlation of Post-Intubation Croup with duration of General Anesthesia in Children undergoing Genitourinary Surgery - Ahmed, Abrar; Rizvi, Syed Ali Mazhar; Sikander, Muhammad Saad; Buland, Khalid; Shareef, Muhammad Huzaifa; Farooq, Muhammad Saad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the effect of intubation time on frequency of post-extubation croup in children undergoing genitourinary surgery.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2022.Methodology: Pediatric participants of either gender aged between 06 months to 12 years, American Society of Anesthesiologists (ASA) Grade I or II planned for elective genitourinary procedures under general anesthesia were included in the trial after obtaining a written informed consent. Stratification sampling technique was used to divide the patients into Group-A with intubation time 01hr. History of respiratory tract infections, characteristics of patients, intubation time, traumatic intubations were the recorded parameters.Results: There were 245(58.1%) vs 177(80.5%) ASA-I patients in Group-A and Group-B respectively, and 35(12.5%) vs 43(19.5%) ASA-II.  In Group-B a total of 11(5%) out of 220 patients developed croup after extubation while only 01(0.4%) out of 280 participants in Group-A experienced post extubation croup. Patients aged 1-4yrs had the highest frequency of croup 07(58.3%). Traumatic intubations and upper respiratory infections were significant factors leading to croup after extubation (p-value